PENGARUH WORK-LIFE BALANCE DAN BEBAN KERJA TERHADAP KEPUASAN KERJA GURU SEKOLAH DASAR ISLAM TERPADU AL-‘ARABI - Siti Nur Amalia; Hasanuddin Hasanuddin; Jumawan Jumawan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine whether work-life balance and workload can affect the job satisfaction of SDIT Al-'Arabi teachers. This research uses quantitative methods with saturated sampling techniques (census), which is one form of non-probability sampling. The research instrument is a questionnaire which is arranged in several statements and measured using a Likert scale. The research population was SDIT Al-'Arabi teachers with a sample of 51 respondents. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach through Smart PLS 4.0 software. The results showed that work-life balance has a positive and significant effect on teacher job satisfaction. Likewise, workload also shows a positive and significant effect on teacher job satisfaction. This study concludes that work-life balance and workload have a positive and significant effect on teacher job satisfaction.